Spatiotemporal heterogeneity and its influencing factors: a perspective on the carbon emissions in China’s beef cattle industry - Sun, Yumeng; Wang, Mingli (Frontiers in Sustainable Food Systems, 2025)
Based on panel data from 31 provinces in China covering the beef cattle industry from 2009 to 2022, this paper constructs a framework for carbon emission measurement and systematically analyzes the spatial and temporal evolution of carbon emissions, the spatial agglomeration effect, and its driving factors in the beef cattle industry using life cycle assessment, Kernel density estimation, Moran’s index, and the spatial Durbin model. The study found that: (1) The total carbon emissions of China’s beef cattle industry exhibit a steady growth trend, with significant regional distribution differences. Emissions grow at a slower rate in the eastern region, while the emission levels in the central and western regions, particularly in the western region, are significantly higher than the national average.1 (2) Carbon emissions exhibit “high-high” and “low-low” spatial agglomeration patterns. Emission reduction is effective in the eastern region, while the central region is gradually catching up. The western region remains the core of high emissions. (3) Carbon emission dynamics indicate a trend of spreading from high-emission regions to peripheral areas, with medium- and small-scale farming regions having greater potential for emission reduction. (4) Improvements in environmental governance, mechanization, and education significantly reduce carbon emissions per unit of beef, driving emission reductions in neighboring regions through spatial spillover effects. Large-scale farming and urban–rural income disparities positively impact carbon emissions, while the role of scientific research inputs in emission reduction remains insignificant in the short term. This study provides a theoretical basis for promoting low-carbon development and regional synergy in the beef industry, suggesting the strengthening of research, development, and promotion of low-carbon technologies, improving the mechanism for regional synergy in emission reduction, and promoting the development of integrated crop-livestock systems to support the realization of the “dual-carbon” goal and the high-quality development of agriculture in the future.